Educação ambiental: re-significação do conceito pelo alunos da 6ª serie do ensino fundamental de um colégio do município de Capanema - SILVA, Michelle Cristini de Araújo (2019)
EA presents itself today as a challenge, and school space for that practice reflected. This study aims to understand to what extent the activities with students from 6th grade contribute to the process of re-construction of knowledge in relation to Environmental Education. My methodological choice was by qualitative research, participant type. The study included a group of sixth grade, composed of 31 students, aged 11 to 12 years residing in the city of Capanema. Used as a tool for data collection, the questionnaire with open and closed questions. In the analyzes considered the responses obtained before the intervention in the classroom and after the intervention. To demonstrate the process of re-building concepts regarding EA considered the verbal and nonverbal developed by students during the interactive situations occurring in the classroom. I found that the design environment initially presented by the students of 6th grade, mostly, was a "naturalist." Most students regarded the environment as a place where living beings, except man, live, along with the presence of abiotic elements. The sources of information for students regarding EA, the vast majority occur through television, internet, magazines, newspapers, and little reference to school. The pedagogical strategies conducted with students from 6th grade contributed to the construction of a training critical and reflective citizen. The school must provide environmental practices that meet both teachers, as students perceive themselves as subjects of their history and of their time, to become social actors as critical citizens reflective of their own actions and the actions of their peers.